Isolasi Jamur Pengurai Pati Dari Tanah Limbah Sagu - Juwita, Dian Ayu; Suharti, Netty; Rasyid, Roslinda (Jurnal Farmasi Andalas, 2013)
Screening of glucoamylase enzyme producing fungi obtained from sago dregs soil at Tapakis district of Padang Pariaman have been done. The screening was conducted by incubating of sample on Potato Dextrose Agar media previously added with starch 1% as an inducer. Incubation was performed during 120 hours at temperature of 20-250C. The existence of glucoamylase enzyme producing fungi were indicated with the disappearance of lugol indicator solution colour around the colonies. It was found that there were 2 isolates of fungi which produced glucoamylase. Following identification, it could be concluded that isolates were Aspergillus sp. and Penicillium sp.